2018
DOI: 10.1108/ijmpb-05-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

The top 10 universal delay factors in construction projects

Abstract: Purpose Projects often face delays and unnecessary use of time due to various factors and reasons, and hence suffer from unfavourable consequences. The purpose of this paper is to identify the universal delay factors from an intensive literature review, complemented by delay factors in major Norwegian construction projects based on empirical data. Design/methodology/approach The study in which this paper is based includes an intensive literature review, and semi-quantitative open survey questionnaires. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 84 publications
7
96
1
6
Order By: Relevance
“…Unique factors (with the frequency of three or less) are: "'Slow decision making process by owner" in Norway [90], UAE [84], and Oman [98]; "Changes in material types and specifications during construction" in Saudi Arabia [102], Turkey [117], and Zambia [113]; "Change/selection of subcontractors in the project" in India [79], Saudi Arabia [112], and Vietnam [105]; "Mobilization delay" in India [127], Malaysia [109], and Malawi [81]; "Site constraints (site blockage, impact of other's land)" in Bangladesh [87], Cambodia [103], and countries with high geopolitical risks [104]; "Impact of subsurface (underground) conditions" in Libya [91], Cambodia [103], and Egypt [123]; "Conflict between parties' in Iran [101], Turkey [70], and Egypt [107]; "Errors in construction" in Iran [93], Zambia [113], and Denmark [89]; "Fluctuation in price of materials" in Saudi Arabia [102] and Ghana [100]; "Conflict between labours" in Saudi Arabia [88] and Zambia [113]; "Labour strikes" in countries with high geopolitical risks [104] and Zambia [113]; "Using inappropriate construction methods" in India [92] and Iran [110]; "Insufficient/inaccurate document preparation" in Turkey [70] and Iran [110]; "Inaccurate first drafts/plan" in Iran [110] and Taiwan [132]; "Delay/weak interaction due to vendor" in India [127] and Oman…”
Section: Key Factors Identified In the Delay Literaturementioning
confidence: 99%
“…Unique factors (with the frequency of three or less) are: "'Slow decision making process by owner" in Norway [90], UAE [84], and Oman [98]; "Changes in material types and specifications during construction" in Saudi Arabia [102], Turkey [117], and Zambia [113]; "Change/selection of subcontractors in the project" in India [79], Saudi Arabia [112], and Vietnam [105]; "Mobilization delay" in India [127], Malaysia [109], and Malawi [81]; "Site constraints (site blockage, impact of other's land)" in Bangladesh [87], Cambodia [103], and countries with high geopolitical risks [104]; "Impact of subsurface (underground) conditions" in Libya [91], Cambodia [103], and Egypt [123]; "Conflict between parties' in Iran [101], Turkey [70], and Egypt [107]; "Errors in construction" in Iran [93], Zambia [113], and Denmark [89]; "Fluctuation in price of materials" in Saudi Arabia [102] and Ghana [100]; "Conflict between labours" in Saudi Arabia [88] and Zambia [113]; "Labour strikes" in countries with high geopolitical risks [104] and Zambia [113]; "Using inappropriate construction methods" in India [92] and Iran [110]; "Insufficient/inaccurate document preparation" in Turkey [70] and Iran [110]; "Inaccurate first drafts/plan" in Iran [110] and Taiwan [132]; "Delay/weak interaction due to vendor" in India [127] and Oman…”
Section: Key Factors Identified In the Delay Literaturementioning
confidence: 99%
“…KPMG's 2019 Annual global construction survey found that for the middle 60% of companies, cost and time overruns still remained a major challenge (KPMG, 2019). At the global level, an analysis of over 104 published research articles related to delays across 45 countries with the intention of identifying the universal top 10 causes of delays revealed that change orders, delays in payments to contractors, poor planning and scheduling, poor site management and supervision, incomplete design, inexperienced contractors, contractor's financial difficulties, owners financial difficulties, resource shortages, and poor labour productivity/shortage of skills were the top universal causes of construction delays (Zidane and Andersen, 2018). Eizakshiri et al (2015) have questioned the 'intentionality' of studying project delays, arguing that researchers are unaware of the intents of the planners involved in planning the schedule for projects.…”
Section: Causes Of Delaysmentioning
confidence: 99%
“…The causes of time overruns differ from project to project and in different situations. The top universal delay factors are delay in payment of contractor(s), poor planning and scheduling, poor site management, design changes during construction, inadequate contractor experience and approaches, sponsor/ owner/client's financial difficulties, improper or incomplete design, poor site management and supervision, shortage of skills and poor productivity (Zidane & Andersen, 2018). According to Ade-ojo and Babalola (2013), major causes are design error, poor site condition, delay in payment, financial incapability of client etc.…”
Section: Causes Of Time Overrunmentioning
confidence: 99%